Expert system for insect pests of agricultural crops - RAVISANKAR, H; SREEDHAR, U; SIVARAJU, K (The Indian Journal of Agricultural Sciences, 2014)
Insect pests are one of the major constraints in agricultural production, processing and storage. The damage caused by insect pests in agriculture is substantial and farmers have to incur huge monetary losses. Management of insect pests is therefore the only solution to save the crops and other valuable inputs that goes into agricultural production. Vast information on insect pests of different crops and their management is available at different sources. Based on this knowledge, a rule based expert system for insect pests of different agricultural crops was developed. The system is supported by a database containing information about 15 crops with a total of 95 insect pests affecting those crops. The expert system was evaluated following the conventional expert system evaluation methodology. This system provides information and solutions to farmers, scientists, extension workers involved in agriculture development and education. Using this system one can identify the pest and diagnose the problem for speedy and effective decision making in pest management to avoid losses.